“Faculty Professional Development – A Virtual Reality?” A Critical Literature Review of Online Communities of Practice in Post- Secondary Settings - Kayon K. Murray-Johnson (Adult Education Research Conference, 2014)
This literature review explores how online communities of practice have served to influence faculty professional practice in diverse settings. Findings indicate that though online CoPs had positive influences including clarity of professional identity, increased reflection and diversified skills, challenges existed that could impede the process. Implications for adult education are also discussed.